Gaps in evidence: Management of pediatric obstructive sleep apnea without tonsillar hypertrophy. (24th November 2015) - Tang, Alice; Gropler, Matthew; Duggins, Angela L.; Amin, Raouf S.; Shott, Sally R.; Chini, Barbara; Ishman, Stacey L.
Abstract : Objectives/Hypothesis: Persistent obstructive sleep apnea (OSA) is demonstrated in 40% of children after adenotonsillectomy. We previously evaluated the basis of management decisions in children with OSA without tonsillar hypertrophy and found that 61% of decisions were non–evidence based. The aim of this study was to identify gaps in evidence for the management of children with OSA without tonsillar hypertrophy. Study Design: Case series. Methods: We recorded all real‐time decisions made by pediatric subspecialists from eight disciplines that participated in an upper airway clinic and management conferences. Practitioners were immediately queried regarding the basis of their decisions, and non–evidence‐based decisions were categorized. Results: During 10 case conferences and five clinics, 507 decisions were made for 63 children (43% with Down syndrome, 20% with Pierre Robin sequence). The 309 non–evidence‐based decisions most commonly pertained to follow‐up timing and appropriate subspecialty clinic location (116/309, 38%) as well as timing for repeat polysomnography (35/309, 11%), especially in children at high risk for persistent OSA after treatment. Additional gaps identified included the likelihood of OSA improvement from weight loss, and effectiveness of sleep surgical procedures (i.e., lingual tonsillectomy, posterior midline glossectomy, and craniofacial surgery) alone or in combination. Conclusions: Identified gaps in evidence included timing and location of follow‐up, appropriate use of polysomnography for surveillance, effectiveness of specific surgical procedures performed alone and in combination, and the use of oral appliances and continuous positive airway pressure therapy in children with Down syndrome. We also found a need for studies to compare the effectiveness of these treatment options in diverse patient populations. Level of Evidence: 4 Laryngoscope, 126:758–762, 2016